The Intervention Scalability Assessment Tool: a pilot study assessing five interventions for scalability - Karen Lee; Andrew Milat; Anne Grunseit; Kathleen Conte; Luke Wolfenden; Adrian Bauman (Sax Institute, 2020)
Objectives: This study tested the utility of the Intervention Scalability Assessment Tool (ISAT) with real-world interventions considered for scale-up in the Australian context. We explored user perceptions of the usefulness of the ISAT in making scalability decisions and conducted an analysis of completed ISATs. Type of program/service: The ISAT was designed to assist policy makers/practitioners to make structured and reflective assessments of the potential scalability of their interventions. Methods: Participants (n = 26) were invited via email and needed to be considering a population intervention for scale-up, to be able to pilot the ISAT, and to be willing to complete an online survey to provide feedback. Survey data and completed ISATs were collated and common responses were identified, with exceptions noted. Results: Thirteen participants accepted the invitation to pilot the ISAT; six completed ISATs and returned surveys and five of each were included in the final analysis. The process by which participants completed the ISAT varied, some involving up to six stakeholders in the process and others only one. The time taken to complete the ISAT ranged from 2 hours to 3 days. Interventions considered for scalability were public health interventions and all but one involved a potential statewide scale-up. In terms of outcome, scalability scores across interventions varied, however, all but one intervention was recommended for scale-up. The remaining intervention was deemed to be promising but further information was required before assessing scalability. Lessons learnt: The ISAT was perceived as a useful tool to assess the scalability of real-world health programs, with participants noting only minor limitations and challenges. The ISAT can be applied to a variety of population health interventions and identifies strengths and weaknesses in the evidence base for scale-up. This study revealed that decisions to scale up are often made despite potential weaknesses highlighted through the ISAT. This is likely a reflection of the critically influential role of contextual factors in decisions to scale up, whereby decision makers may balance a variety of considerations, of which evidence of scalability is only one factor.